The Most Negative Life Expectation of College Students - Warner, Ronald E. (Canadian Journal of Counselling and Psychotherapy, 2011)
In a 1972 American study college students were asked to describe in writing their two most negative life experiences. These were defined as, "experiences that made your life worse or were a negative force in your development." Incidents involving teachers were reported by subjects more often than any other persons or events. More than ten years later, the author replicated the above mentioned study at a Canadian urban university and found very similar results. The purpose of this investigation was to replicate these studies, but with the major difference of using in-depth telephone interviews. Subjects were also asked some health related questions. The 208 volunteer college students reported that their negative experiences most frequently involved illness/injury, parents, and death (in that order). Interactions with teachers were at the bottom of the list. It is recommended that because of major research design deviations, the present investigation be viewed with caution as a replication study. Further research is needed before minimizing or dismissing the serious implications of the two previous studies.